Heterogeneity amongst lymph-borne "dendritic" cells. - Macpherson, G; Pugh, C (1984)
Thoracic duct lymph from mesenteric lymphadenectomized rats contains a population of non-lymphocytic, irregularly shaped, Ia-positive cells. These cells are able to stimulate an allogeneic or syngeneic MLR, can act as accessory cells in Concanavalin A-induced lymphocyte mitogenesis and can stimulate the rejection of enhanced allografts. They are thus similar to dendritic cells isolated from lymphoid and peripheral tissues. These cells are not endocytic or glass adherent and do not bear C3 receptors or mannose-fucose receptors. They may possess weak Fc receptor activity. In terms of morphology, cytochemistry and surface markers these cells show marked heterogeneity. The nature of this heterogeneity is described and the relationship of these cells to other potential accessory cells is discussed in terms of lineage and function.